Methicillin-Resistant Staphylococcus aureus Prostatic Abscess in a Liver Transplant Recipient. (20th October 2014) - Jana, Tanima; Machicado, Jorge D.; Davogustto, Giovanni E.; Pan, Jen-Jung
Abstract : Prostatic abscesses are usually related to gram-negative bacilli. However, methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a substantial cause of prostatic abscesses in recent years. Herein, we report the case of a 31-year-old man with a history of orthotopic liver transplantation 10 years ago who presented with acute onset dysuria and abdominal pain and was diagnosed with a MRSA prostatic abscess. To our knowledge, this is the first case describing a prostatic abscess in a liver transplant recipient and the first reporting MRSA as the causative organism of a prostatic abscess in a solid organ transplant recipient.